Pengaruh Customer Experience Dan Customer Expectations Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Sebagai Variabel Intervening (Studi Kasus Pada Konsumen Toyota Kota Malang) - Kurniawan, Ivan Fachrur; Nurhajati, Nurhajati; Khalikussabir, Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This research aims to analyze and describe the influence of customer experience and customer expectations on customer loyalty through customer satisfaction as an intervening variable (a case study of Toyota consumers in Malang City). The population used in this research is Toyota consumers in Malang City. The sample in this study used the hair formula obtained from 140 people. This research analyzes data using Structural Equation Modeling (SEM) techniques with the help of SmartPLS software version 4.1.0.9. The variables used in this research are customer loyalty as the dependent variable, customer satisfaction as the mediating variable, customer experience, customer expectations as the independent variable. The research results show that 1) Customer experience has an effect on customer loyalty but is not significant 2) Customer Expectations have a positive and significant effect on customer loyalty 3) Customer Experience has a positive and significant effect on customer satisfaction 4) Customer expectations have a positive and significant effect on customer satisfaction 5) Customer satisfaction has a positive and significant effect on customer loyalty 6) Customer experience has a positive and significant effect on customer loyalty through customer satisfaction as an intervening variable 7) Customer expectations have a positive and significant effect on customer loyalty through customer satisfaction as an intervening variable. Keywords: Customer Loyalty, Customer Satisfaction, Customer Experience, Customer Expectations.